The Pedagogical Use of Didactic Classes for Teaching Cognitive Psychology - Madsen, Jens Koed; George, Nicole Lauren; Cury Fernandes, Andreia (Teaching and Learning Inquiry, 2024)
The didactic class is a pedagogical tool meant to increase classroom interactivity by encouraging student discussion of real-life cases in connection with theory. This paper evaluates the pedagogical impact of using a one-off didactic class where an external expert is brought in to discuss how to relate a cognitive psychology course’s content to real-life problems. Using a mixed-methods approach, we measure the undergraduate students’ sense of conceptual understanding, their perspective on applying cognitive sciences, their sense of belonging to the department, and their motivation to work. Students’ sense of understanding and their perspective in applying cognitive sciences to real-world problems significantly increased after this class. However, we found no significant differences in their sense of belonging to the department or their motivation to study. This suggests didactic classes may further course-specific content but do not change broader aspects of motivation or belonging. The qualitative interviews support the quantitative results. Students reported that didactic class made them think laterally about content from other modules and how they could apply theoretical insights to real-world problems, which boosted confidence. Students reported great satisfaction with the didactic class. Of course, the speaker must be relevant to the course content, and students should feel empowered and able to speak in class. However, these are practical concerns that should not discourage lecturers from exploring didactic classes as a fun and instructive tool that has significant pedagogical benefits. Read the corresponding ISSOTL blog post here.